Analisis Faktor Dominan yang Mempengaruhi Peran Keluarga dalam Pencegahan Penularan TB di Desa Kambatatana - Gunawan, Yosephina E S; Landi, Melkisedek; Pekabanda, Kartini; Mulu, Servasius To'o Jala; Radandima, Ester; Mosa, Erlin Rambu Dulu (JURNAL KESEHATAN PRIMER, 2022)
Introduction: Pulmonary tuberculosis is a contagious disease that requires a long treatment period, making family support crucial in the healing process. Objective: This study aims to explain the role of the family in preventing the transmission of pulmonary tuberculosis within the family at Kawangu Health Center, Kambatatana Village. Methods: This research used a descriptive design with total sampling as the sampling technique. The instrument used in this study was a questionnaire. Results: The study findings revealed that the role of the family in medication assistance was reported by 18 participants (78%), the role of the family in using personal protective equipment (PPE) was reported by 14 participants (61%), the role of the family in maintaining environmental cleanliness was reported by 22 participants (96%), and the role of the family in meeting nutritional needs was reported by 17 participants (74%).